INTERRELATIONSHIP OF MATHEMATICS WITH PHYSICS - Tursunov Ikrom Eshpo‘latovich (Journals Park Publishing, 2023)
This article is dedicated to explaining the relationship between mathematics and physics, the importance of using the integration of physics and mathematics, and finding solutions to physical problems using mathematical concepts. It contains information about the uniqueness of the content of mathematics, the relationship between mathematics and physics. It is also explained how to find solutions to physical problems with the help of derivatives, integrals, systems of equations and vectors from mathematical concepts.
Keywords: integration of sciences, derivative, integral, system of equations, vector, physical problem.